2004
DOI: 10.1007/978-3-540-27780-4_6
|View full text |Cite
|
Sign up to set email alerts
|

Social Adaptive Navigation Support for Open Corpus Electronic Textbooks

Abstract: Abstract.Closed corpus AH systems demonstrate what is possible to achieve with adaptive hypermedia technologies; however they are impractical for dealing with the large volume of open corpus resources. Our system, Knowledge Sea II, presented in this paper explores social adaptive navigation support, an approach for providing personalized guidance in the open corpus context. Following the ideas of social navigation, we have attempted to organize a personalized navigation support that is based on past learners' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 16 publications
0
82
0
2
Order By: Relevance
“…This kind of SNS helped the learners to clearly recognize the most and the least visited pages and guide their navigational choices appropriately. Our classroom study [2] demonstrated that a footprint-based SNS is able to increase the usage of open corpus resources and that the learners appreciate it immensely. At the same time, a few students pointed out that the number of visits to a page is not always a reliable measure of its relevance to their needs and asked for better relevance indicators.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…This kind of SNS helped the learners to clearly recognize the most and the least visited pages and guide their navigational choices appropriately. Our classroom study [2] demonstrated that a footprint-based SNS is able to increase the usage of open corpus resources and that the learners appreciate it immensely. At the same time, a few students pointed out that the number of visits to a page is not always a reliable measure of its relevance to their needs and asked for better relevance indicators.…”
Section: Introductionmentioning
confidence: 86%
“…1), which combined the use of a self-organized knowledge map [3] with a simple "footprint" SNS [2]. The first version of KSII provided a simple interface for annotating tutorial pages by adding written notes.…”
Section: Annotation-based Social Navigation Support In Knowledge Seamentioning
confidence: 99%
See 2 more Smart Citations
“…One research stream focused on the versatility of LMS, attempting to provide in one system as many teacher and learner support features (from content authoring to quizzes to discussion forums) as provided by a modern LMS --plus, the ability to adapt to the user (Morimoto et al, 2007;Specht et al, 2002;Ueno, 2005 (Brusilovsky, Chavan & Farzan, 2004;Brusilovsky & Henze, 2007;Henze & Nejdl, 2001). Most recent projects, however, choose not to compete with present-day LMS, but instead to focus on adaptive features of the coming generation of Web-based educational systems.…”
Section: Adaptive Educational Hypermedia: the Third Generationmentioning
confidence: 99%